2013
DOI: 10.1186/2251-6581-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Medical risk factors of diabetes mellitus among professional drivers

Abstract: BackgroundRoad transport drivers are one of the professional groups whose activities have a strong impact of public safety. In view of the natural professional activity, the drivers are at a higher risk of obesity, hypertension and hyperlipidemia, and carbohydrate metabolism disorders such as diabetes mellitus.Materials and methodsMedical documentation was the source of data for the reported study. It derived from medical examinations of 1903 drivers applying for driving license.ResultsHyperglycemia was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
5
17
3
3
Order By: Relevance
“…No significant correlations were observed between the all parameters mentioned in the Table 2 (FBS, BMI, systolic blood pressure and diastolic blood pressure, cholesterol and triglycerides) except the age with hearing loss (P > 0.05). However, the prevalence of increased blood pressure was increased with increasing age, that this results has been reported in other studies (16). The mean values of systolic blood pressure and diastolic blood pressure and FBS had a normal range.…”
Section: Discussioncontrasting
confidence: 43%
“…No significant correlations were observed between the all parameters mentioned in the Table 2 (FBS, BMI, systolic blood pressure and diastolic blood pressure, cholesterol and triglycerides) except the age with hearing loss (P > 0.05). However, the prevalence of increased blood pressure was increased with increasing age, that this results has been reported in other studies (16). The mean values of systolic blood pressure and diastolic blood pressure and FBS had a normal range.…”
Section: Discussioncontrasting
confidence: 43%
“…The study of Izadi et al in Theran in 2010 and 2011 among the bus and truck drivers revealed that 20.8% were with obesity. 9 In a study conducted by Saberi and others in Iran in 2011, 41% were with overweight and 23% were found to be with obesity. 10 In a study conducted by Mohebbi and others in Iranian professional drivers in 2012, overweight was found to be 41.4% cases and obesity was found to be 21.3%.…”
Section: Discussionmentioning
confidence: 97%
“…Certain aspects of the lifestyle of commercial drivers, such as the sedentary nature of the occupation and limited healthy food choices on the road, are associated with increased risk of developing diabetes [12,13]. The National Survey of Long-Haul Truck Driver Health and Injury, conducted by the National Institute for Occupational Safety and Health, found that the self-reported prevalence of diabetes was 14.4% among US long-haul truck drivers but was 6.7% in working adults (based on the 2010 National Health Interview Survey) [14].…”
Section: Introductionmentioning
confidence: 99%